Establishing a database of mosques in Sabha using GIS (Journal of Human Sciences, 2021)
This research aims to highlight the importance of geographic information systems as a spatial database that allows data, processing and analysis, to solve problems. It focuses on providing support to decision-makers to manage mosques. This happens through the establishment of a database of mosques in the city of Sabha. It also works to provide management and view the analysis available to stand on the pattern of mosque distribution. It is done to investigate the efficiency of geographical distribution and to identify suitable places for the establishment of new mosques. The research was based on the descriptive-analytical method. It showed the enormous possibilities available in GIS to manage and analyse mosque data. This process facilitates the work and supports the decision-making of the Ministry of Awqaf. GIS analysis can show geographic distribution, query-specific characteristics, perform the measurement, summarize and convert data, as well as to detect patterns, and perform suitability analysis. It turned out that the geographical distribution of mosques takes the form of cluster and the direction of distribution south-east-northwest. It was also found that there is an overlap in the scope of the influence of mosques, reflecting the poor geographical distribution of mosques in the city. About 42.4% of the urban area is outside the service of existing mosques. Therefore, its residents do not have easy access. Areas suitable for the establishment of new mosques have also been identified.